A scoping review of job search self-efficacy over the past 5 years: antecedents, mechanisms, consequences, and future directions based on SCT/SCCT - Zheng, Xiaojian; Mohd Puad, Mohd Hazwan; Ab. Jalil, Habibah (Frontiers in Psychology, 2025)
Against the backdrop of global labor market volatility, Job Search Self-Efficacy (JSSE) is critical for job seekers’ persistence and success. Guided by Social Cognitive Theory (SCT) and Social Cognitive Career Theory (SCCT), this scoping review synthesizes 22 empirical studies (2019–February 2025) to address three core questions: JSSE’s antecedents, intervention mechanisms, and consequences. The results showed the following: (1) antecedents concentrated on individual traits (e.g., career adaptability, emotional intelligence) and contextual support (e.g., mentoring, positive job search events); (2) intervention mechanisms were dominated by simple mediation (e.g., JSSE mediating perceived employability and job search behavior) and single moderation (e.g., extraversion moderating JSSE-success links); and (3) consequences focused almost exclusively on short-term outcomes (e.g., job search intensity, job offers). Key gaps include homogeneous samples (over-reliance on university students), methodological limitations (dominant cross-sectional designs), and understudied long-term career/emotional consequences. This review strengthens the JSSE’s theoretical connection to SCT/SCCT and provides targeted guidance for interventions while outlining directions for more inclusive and rigorous future research.